The Numerical Simulation in Ballistics - Pincevičius, A.; Rakauskas, R. J.; Misevičius, G. (Nonlinear Analysis: Modelling and Control, 2001)
In this paper we examine the movement of the solid body thrown with some angle to the horizon (for example the shot mine). Such movement is described by non-linear system of equations. This system is being approximated by linear system, in segments. The experiment results have been approximated and the dependence of air resistance coefficient from mean value of velocity along the trajectory was found. From the point of view of mathematics the incorrect problem must be solved because the initial conditions of system corresponding to fixed values of solutions (the coordinates of target points) must been estimated. In the case of linear system it is possible to examine the influence of non-large increment of initial conditions to the final result. In this work the probability of destruction of some fixed target and the mean square deviation of shooting regression. On the other hand has been estimated the possibility of destruction of group target using the method of Monte-Carlo.